Penyelenggaraan Kesehatan Berdasarkan Peraturan Daerah Provinsi Riau Nomor 4 Tahun 2020 di Kecamatan Kerinci Kanan Kabupaten Siak - Adrian Faridhi; Sudi Fahmi; Alexsander Yandra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has hit all countries in the world and Indonesia is no exception, the Regional Government issues regional regulations to prevent the spread of Covid-19, the Riau Provincial Government issues Regional Regulation Number 4 of 2020 concerning Health Implementation. Partners need legal information on activities and can avoid legal sanctions, both fines and imprisonment, implementation methods by distributing questionnaires to participants before and after implementation, the issue of health protocol enforcement is a central issue among efforts to prevent the transmission of Covid-19.